Screening for Information Environments: A Role for Health Systems to Address the Misinformation Crisis - David Scales; Jack Gorman (Journal of Primary Care & Community Health, 2022)
Misinformation about health topics is a public health issue. We are bombarded with information from many sources, across many digital means of communication, affecting the ways in which we are born, grow, work, live, and age. This makes information environments a social determinant of health (SDoH), but one not currently adequately addressed by clinical or public health practitioners. Since health systems are already screening for social determinants of health, existing mechanisms can additionally screen for unhealthy information environments. Then, for those patients who screen positive, we can apply best practices learned from initiatives addressing vaccine hesitancy: providing a non-judgmental environment in which to discuss health beliefs, using motivational interviewing techniques to gage patient perspectives and readiness for change, and taking a harm-reduction approach in recognizing that behavior change evolves over time. Displacing misinformation is a process, not an event. As such, we need to address the underlying psychological and sociological reasons that people maintain unscientific beliefs as we would hope to do with any other SDoH. Furthermore, as information environments are the product of both individual choices and structural factors, clinicians should approach patients immersed in unhealthy information environments without blame or ostracism, much as we would approach any patient adversely impacted by social determinants of health.